PENGEMBANGAN BAHAN AJAR BERBASIS KEARIFAN LOKALTERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI IPAS KELAS V SD ISTIANAH TERPADU KOTA SORONG - Rahmawati, Sri Putri; Rokhman, Fathur; Yuwono, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is based on the needs of students in the classroom, students experience diffulties in learning science material, especially in material such as what is the culture of my region, which causes student learning outcomes to not be optimal. This research aims to: 1) Analyze the development of local wisdom-based teaching materials on the cognitive learning outcomes of elementri school students. 2)Analyze the feasibility of developing lokal wisdom-based teaching materials on the cognitive learning outcomes of elementary school students. 3). Analyze the effectiveness of developing local wisdom-based teaching materials for elementary school students’ learning aoutcomes. The type of research used is research and development (R&D) with ADDIE development procedures, namely Analyze, Design, Development, Implementation and Evaluation. The data collection techniques used are observation, interviews, questionnaires, and tests. The data analysis techiques used are qualitative and quantitative data analysis techniques. Research subjects fot class V of Istianah Intgrated Elementary School. This research shows the results of the validation of teaching materials based on 95,45% media validators and 100% material validators from both validators including materials was obtained from the average pretest score of 51.25%, while the posttest averafe score increased by 82.6%, ane the N-Gain test obtained a score of 0.64%. quite effective category. This shows that local wisdom-based teaching materials are suitable for use.